Graded-Index Fluoropolymer Antireflection Coatings for Invisible Plastic Optics - Wang, Baomin; Ruud, Christian J; Price, Jared S; Kim, Hoyeon; Giebink, Noel C (Nano letters, 2019)
Plastic optics are used in an ever-expanding range of applications and yet a durable, high performance antireflection (AR) coating remains elusive for this material class. Here, we introduce a sacrificial porogen approach to produce ultralow refractive index nanoporous fluoropolymer AR coatings via thermal coevaporation of Teflon AF and the small molecule N,N′-bis(3-methylphenyl)-N,N′-diphenylbenzidine (NPD). Using this approach, we demonstrate a five-layer, step-graded AR coating that reduces the solar spectrum-averaged (400 < λ < 2000 nm) reflectance of acrylic plastic to <0.5% for incidence angles up to 40° and withstands over 3 months of outdoor rooftop exposure with minimal degradation. A trilayer coating optimized for the visible range yields luminous reflectivity down to ∼0.1%, effectively rendering double-side coated acrylic plastic invisible under room lighting conditions. Strong adhesion to most optical plastics, an outstanding combination of mechanical, chemical, and environmental durability, and compatibility with commercial vacuum coating systems should enable this AR technology to find widespread practical use.